On the effectiveness of virtual reality-based training for surgical robot setup - Mehrfard, Arian; Fotouhi, Javad; Forster, Tess; Taylor, Giacomo; Fer, Danyal; Nagle, Deborah; Armand, Mehran; Navab, Nassir; Fuerst, Bernhard (Computer Methods in Biomechanics and Biomedical Engineering : Imaging & Visualization, 2021)
Virtual Reality (VR) is rapidly increasing in popularity as a teaching tool. It allows the creation of a highly immersive, three-dimensional virtual environment. With more robots saturating the industry, there is a need to train end-users on how to set up, operate, tear down, and troubleshoot the robot. While VR has become widely used in training surgeons on the psychomotor skills associated with operating the robot, little research has been done to see how the benefits of VR could translate to teaching the bedside staff, tasked with supporting the robot during the surgical procedure. We trained 30 participants on how to set up a robotic arm in an environment mimicking clinical setup. We divided these participants into three groups with one group trained with paper-based instructions, one with video-based instructions and one with VR-based instructions. We then compared these three different training methods. VR and paper were highly favoured training mediums over video. VR-trained participants achieved slightly higher fidelity of robotic joint angles, suggesting better comprehension of the spatial awareness skills necessary to achieve desired arm positioning. In addition, VR resulted in higher reproducibility of setup fidelity and more consistency in user confidence levels.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Medical training; surgical robotics; virtual reality